2014
DOI: 10.3390/molecules190811341
|View full text |Cite
|
Sign up to set email alerts
|

Two New Acylated Flavonol Glycosides from the Seeds of Lepidium sativum

Abstract: Two new acylated flavonol glycosides named kaempferol

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…O-α-L rhamnopyranoside was identified by Fan et al [7]. However, while the same acylation was present in the Algerian variety, quercetin was replaced by a kaempferol.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…O-α-L rhamnopyranoside was identified by Fan et al [7]. However, while the same acylation was present in the Algerian variety, quercetin was replaced by a kaempferol.…”
Section: Discussionmentioning
confidence: 64%
“…The differential activities of flavonoids could depend on the solvent used for extraction and on the position of substituents in the flavonoid nucleus. These differences in substituents give rise to the major bioactive compounds such as quercetine, kampferol and their glycosides which are present in Lepidium sativum seeds [7,[15][16][17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its main fatty acids are oleic acid (30%) and α-linolenic acid (32%) representing the n-3 group. Cress seeds also contain a high level of polyphenols and are a source of bioactive glycosides [15,19]. It has been found that the isoflavone glycoside isolated from L. sativum seeds can improve liver function and the serum lipid profile.…”
Section: Introductionmentioning
confidence: 99%
“…This effect appears to be related to the increased urinary elimination of sodium, potassium, and chlorides (Maghrani et al, 2005 ; Table 5 ). Recently, two new glycosides isolated from seeds of L. sativum were shown to have an anti-inflammatory potential (Fan et al, 2014 ). Another member of the Lepidium genus is Lepidium latifolium , commonly known as broadleaved pepper weed.…”
Section: Herbs and Spices Less Commonly Used For Treatment Of Hypertementioning
confidence: 99%